O imperador em folhetins: a monarquia brasileira e D. Pedro II nos rodapés da Gazeta de Notícias (1879-1882) - Bento, Elias Ferreira (2021)
On the morning of March 18, 1882, the Brazilian Court was surprised by the information that thieves acquired entered the Palace of São Cristóvão, the official residence of Emperor D. Pedro II, and stole several jewels belonging to the Brazilian crown. The Rio de Janeiro press soon returned to the subject and passed on to all the developments of the police investigations. The jewels were quickly found, buried in the home of one of the perpetrators. However, returned from the stolen objects, all those involved were left free, without any kind of punishment. The imperial family, at first treated as a victim, then began to be the target of heavy criticism from some press organs, conveyed through comic texts, collections, illustrated chronicles and even through literature. The case left the private sphere and moved to the political sphere, as it is used as an excuse to discuss agendas dear to opponents of the monarchy. Taking the press of the period as an object, the present work intends to analyze how different impressions appropriated the crime episode in order to convert it into a political fact, attacking, mainly, the image of the Emperor.